To Solve the Challenges of Coal Export Issues by Marine Terminals in the Primorsky Region by Analysis of Cargo Handling Technology. Issue 3 (1st February 2022) - Romanova, G; Pesterev, S; Romanov, A
Abstract: since 2010, the stevedoring companies in the Primorsky region have been actively increasing the volumes of coal handling due to growing demand for coal production (in 2.5 times) in the countries of the Asia-Pacific region. At ¼ 2020, in the context of the stagnation of the global economy, the demand for coal remained stable in the countries of the Asia-Pacific region. Thus, in order to maintain the positions of the Russian Federation in the coal markets of the Asia-Pacific region countries, it is necessary to have due understanding of the handling capacities efficiency, the quality of coal processing services and the environmental impact in the seaports of the Primorsky region. Despite the fact that the closed coal handling technology at the specialized coal terminal used by JSC «Vostochny Port» is considered the most effective, the most local stevedoring companies use non-specialized coal handling technology by clamshells.